A class B heat shock factor selected for during soybean domestication contributes to salt tolerance by promoting flavonoid biosynthesis. Issue 1 (1st October 2019) - Bian, Xiao‐Hua; Li, Wei; Niu, Can‐Fang; Wei, Wei; Hu, Yang; Han, Jia‐Qi; Lu, Xiang; Tao, Jian‐Jun; Jin, Meng; Qin, Hao; Zhou, Bin; Zhang, Wan‐Ke; et al.
Summary: Soybean ( Glycine max ) production is severely affected in unfavorable environments. Identification of the regulatory factors conferring stress tolerance would facilitate soybean breeding. In this study, through coexpression network analysis of salt‐tolerant wild soybeans, together with molecular and genetic approaches, we revealed a previously unidentified function of a class B heat shock factor, HSFB2b, in soybean salt stress response. We showed that HSFB2b improves salt tolerance through the promotion of flavonoid accumulation by activating one subset of flavonoid biosynthesis‐related genes and by inhibiting the repressor gene GmNAC2 to release another subset of genes in the flavonoid biosynthesis pathway. Moreover, four promoter haplotypes of HSFB2b were identified from wild and cultivated soybeans. Promoter haplotype II from salt‐tolerant wild soybean Y20, with high promoter activity under salt stress, is probably selected for during domestication. Another promoter haplotype, III, from salt‐tolerant wild soybean Y55, had the highest promoter activity under salt stress, had a low distribution frequency and may be subjected to the next wave of selection. Together, our results revealed the mechanism of HSFB2b in soybean salt stress tolerance. Its promoter variations were identified, and the haplotype with high activity may be adopted for breeding better soybean cultivars that are adapted to stress conditions.